1990
DOI: 10.1002/star.19900421203
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Properties of Canna edulis Starch — Comparison with Maize Starch

Abstract: Starch from the rhizomes of Canna edulis was isolated, purified and its physico‐chemical properties are compared with maize starch. Scanning electron microscopy of the granules show that they are oval to eliptical in shape. It has low contents of lipids, ash and proteins, and has significantly higher content of amylose. It displays low water‐binding capacity and gelatinization temperature. Swelling and solubility are higher when compared with maize starch. Brabender viscosity of C. edulis starch is more than t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
6

Year Published

2000
2000
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 13 publications
1
19
0
6
Order By: Relevance
“…The starches presented a great difference in their amylose content (Table 2) [12,13,38] and normal [9,14,28] amylose content have been reported for C. indica starches. M. esculenta amylose content was within the ranges reported previously [34], whereas for X. sagittifolium higher amylose content (23-35%) have been reported [8,11,35].…”
Section: Amylose Contentmentioning
confidence: 86%
“…The starches presented a great difference in their amylose content (Table 2) [12,13,38] and normal [9,14,28] amylose content have been reported for C. indica starches. M. esculenta amylose content was within the ranges reported previously [34], whereas for X. sagittifolium higher amylose content (23-35%) have been reported [8,11,35].…”
Section: Amylose Contentmentioning
confidence: 86%
“…Studies on physicochemical properties (Table 2) revealed that canna starch has good potential in food application because of its high viscosity, gel strength, and high phosphorus content [71][72][73]. Hermann [73] reported that the bakery products prepared from canna starch are much lighter, crispier, and tastier than those from wheat.…”
Section: Canna (Queensland Arrowroot)mentioning
confidence: 99%
“…Hermann [73] reported that the bakery products prepared from canna starch are much lighter, crispier, and tastier than those from wheat. These physicochemical properties could make canna starch valuable as excipients in pharmaceutical formulations [72].…”
Section: Canna (Queensland Arrowroot)mentioning
confidence: 99%
“…El almidón de yuca fue el que presentó la mejor estabilidad a los procesos de refrigeración y congelación (0 y 3,2% de sinéresis, respectivamente). Soni et al (1990) mencionan que cuando los almidones se someten a sucesivos ciclos de congelación, su estructura se ve afectada, ya que hay una redistribución y dilución de las pastas de almidón por el crecimiento y disolución de los cristales de hielo. Este comportamiento se dió en el almidón de makal, por haber presentado una baja estabilidad a los procesos de refrigeración y congelación, ocasionando la pérdida del agua atrapada en el gel.…”
Section: Caracterización Funcionalunclassified